Experimental and theoretical investigations of free radical photopolymerization: Inhibition and termination reactions. (3rd January 2019) - Christmann, Julien; Ley, Christian; Allonas, Xavier; Ibrahim, Ahmad; Croutxé-Barghorn, Céline
Abstract: In this work, the inhibition and termination reactions occurring throughout a free radical photopolymerization initiated by a type-I photoinitiator are studied by kinetic modeling. The role of the macroradicals as the main oxygen trapping agents during the inhibition time is identified, and the absence of primary radical consumption by oxygen can be related to a high initiation efficiency at early times. The ratio of the termination reactions reveals that bimolecular termination remains the principal pathway for the cessation of macromolecule growth, even at high polymer conversion. Moreover, the evolution of the termination ratio during the polymerization can be correlated to both the diffusional control of the polymerization reactions as the polymer network grows and the photoinitiator consumption. Finally, the effect of the incident light intensity and the initial photoinitiator concentration on the termination reactions is assessed, and the validity of the steady-state assumption applied to the macroradical concentration discussed. Graphical abstract: Highlights: Kinetic modeling is useful to study inhibition and termination reactions. Macroradicals are the principal oxygen trapping agents throughout the inhibition. The ratio of the termination pathways evolves during the photopolymerization reaction. Bimolecular termination is the main termination reaction all along the process. Incident intensity and photoinitiator concentration affect the termination ratio.